Lung behavior during a staircase high-frequency oscillatory ventilation recruitment maneuver - de Jager, Pauline; Koopman, Alette A.; Markhorst, Dick G.; Kneyber, Martin C. J. (Intensive care medicine experimental, 2024)
Background Lung volume optimization maneuvers (LVOM) are necessary to make physiologic use of high-frequency oscillatory ventilation (HFOV), but lung behavior during such maneuvers has not been studied to determine lung volume changes after initiation of HFOV, to quantify recruitment versus derecruitment during the LVOM and to calculate the time to stabilization after a pressure change. Methods We performed a secondary analysis of prospectively collected data in subjects < 18 years on HFOV. Uncalibrated respiratory inductance plethysmography (RIP) tracings were used to quantify lung recruitment and derecruitment during the LVOM inflation and deflation. The time constant was calculated according to the Niemann model. Results RIP data of 51 subjects (median age 3.5 [1.7–13.3] months) with moderate-to-severe pediatric acute respiratory distress syndrome (PARDS) in 85.4% were analyzed. Lung recruitment and derecruitment occurred during the LVOM inflation phase upon start of HFOV and between and within pressure changes. At 90% of maximum inflation pressure, lung derecruitment already started during the deflation phase. Time to stable lung volume (time constant) could only be calculated in 26.2% of all pressure changes during the inflation and in 21.4% during the deflation phase, independent of continuous distending pressure (CDP). Inability to calculate the time constant was due to lack of stabilization of the RIP signal or no change in any direction. Conclusions Significant heterogeneity in lung behavior during a staircase incremental–decremental LVOM occurred, underscoring the need for higher initial inflation pressures when transitioning from conventional mechanical ventilation (CMV) and a longer time between pressure changes to allow for equilibration.